2005
DOI: 10.1016/j.jhsb.2005.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The Porcine Forelimb as a Model for Human Flexor Tendon Surgery

Abstract: Technical skills have been shown to transfer very well from bench models to practical use. The central two rays of 30 forelimbs of pigs were dissected and anatomical observations were made. The rays contained deep and superficial flexor tendons enclosed in a fibro-osseous tunnel and these were present in all 60 specimens. The fibrous part of the tunnel had specific constant condensations in annular and oblique directions which were present in all 60 rays. The anatomy of the porcine forelimb digital flexor tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 6 publications
2
37
0
1
Order By: Relevance
“…Pig flexor tendons are recommended by anatomical studies [9] and commonly used for biomechanical testing of flexor tendon suture techniques [10][11][12][13]. Other authors used canine flexor tendons [14][15][16] or sheep tendons [17] but did not report on the native strength of such tendons.…”
Section: Discussionmentioning
confidence: 99%
“…Pig flexor tendons are recommended by anatomical studies [9] and commonly used for biomechanical testing of flexor tendon suture techniques [10][11][12][13]. Other authors used canine flexor tendons [14][15][16] or sheep tendons [17] but did not report on the native strength of such tendons.…”
Section: Discussionmentioning
confidence: 99%
“…9,25 As described in prior studies, the tendons were harvested from the 2 central rays of each forelimb and transected 5 mm proximal to the long vinculum, within the Zone II region. 4,12,17,21 Tendons were visually inspected, and those with grossly deviating size or deformities were excluded. The 3 test groups consisted of the following: Adelaide type core repair was conducted using the suture with 4-mm cross-locks and 1-cm suture purchase with a buried 6-throw square knot in PDS™ repairs, and a knotless, modified Adelaide repair was performed using the barbed sutures, terminating in a reverse throw per manufacturer recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…We chose porcine forelimbs flexor tendons for this study because they were readily available and cost-effective and have been shown to offer a comparable model for human tendons for the study of flexor tendon repair. 23,24 We harvested and randomized 47 fresh porcine flexor tendons from the central 2 rays of the forefeet. All tendons were continuously stored in saline solutionesoaked gauze compress pouches to preserve the tissue uniformly.…”
Section: Methodsmentioning
confidence: 99%